The HLA‐B*15:400N allele identified in a volunteer donor for hematopoietic stem cell transplant. (29th June 2018) - Baek, I.‐C.; Choi, E.‐J.; Shin, D.‐H.; Kim, H.‐J.; Kim, T.‐G.
Abstract : HLA‐B*15:400N differs from HLA‐B*15:01:01:01 by nucleotide deletions from position 328 to 331 in exon 3.